The Resilience Power and Existence of Pesantren Lirboyo and Al-Falah Kediri During the Post-Covid 19 Pandemic - Fanani, Moh. Zainal (Didaktika Religia, 2022)
This study looks at how Pesantren Lirboyo and al-Falah Ploso in Kediri have kept going during the pandemic. It looks at how these institutions have become more resilient. This study uses a qualitative approach, with the subjects being Pesantren Lirboyo and al-Falah Ploso in Kediri. The findings showed that Pesantren Lirboyo and Ploso Kediri have taken the following steps to make their pesantren more resilient: The strategy used by Pesantren Lirboyo and Al-Falah Ploso in Kediri to stay strong during the pandemic has several key parts. These include keeping the cottage clean and following health rules, using indicators of a strong pesantren, getting support from the government, preparing students who will return to the pesantren, and working with the covid task force. 2) Pesantren Lirboyo and Ploso in Kediri have made these efforts to become more resilient: A healthy pesantren, prepared human resources, sufficient budgets, students understand the indicators of resilience, students adopt a lifestyle, cottage environment is clean. The preparation of health facilities, the support of students’ guardians, and the instilling of belief in students that the outbreak of the Corona Virus Disease 2019 (Covid-19) is a test from Allah. 3) Lirboyo and Ploso in Kediri face challenges in becoming a more resilient pesantren. These include difficulties in implementing health protocols, a lack of familiarity with online learning, the lengthy process of returning students to pesantren, and the absence of dedicated facilities for student quarantine.